1998
DOI: 10.1111/j.1365-2338.1998.tb00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and transmission of Ralstonia solanacearum in aquatic plants of Solatium dulcamara and associated surface water in England1

Abstract: An isolated outbreak of brown-rot disease of ware potatoes, caused by Ralstonia solanacearum biovar 2A, was reported for the first time in England in 1992. A second isolated outbreak was detected in 1996 as a result of random testing of ware potatoes for latent infection. Both outbreaks were associated with the use of irrigation water from sources in which infected Solanum dulcamara was found to be growing. Methods involving indirect ELISA, polymerase chain reaction (PCR) and culture on semi-selective media we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
3
27
0
1
Order By: Relevance
“…In 2001, R. solanacearum was detectable by plating in summer and again became nondetectable in November. These results agree with previous studies in the United Kingdom and The Netherlands, where the levels of this bacterium in waterways were usually 10 cells/ ml, dropping below the detection limit when exposed to cold temperatures (12,22). Higher densities (10 3 cells/ml) have been described in the summer in The Netherlands, probably due to the proximity of the sampled sites to industrial plants for potato processing (21).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In 2001, R. solanacearum was detectable by plating in summer and again became nondetectable in November. These results agree with previous studies in the United Kingdom and The Netherlands, where the levels of this bacterium in waterways were usually 10 cells/ ml, dropping below the detection limit when exposed to cold temperatures (12,22). Higher densities (10 3 cells/ml) have been described in the summer in The Netherlands, probably due to the proximity of the sampled sites to industrial plants for potato processing (21).…”
Section: Discussionsupporting
confidence: 82%
“…An investigation of the population densities of R. solanacearum during the first 2 years of analyses at five sites on a Spanish river associated with an outbreak of bacterial wilt in potato plants has demonstrated that the isolation of this pathogen on solid media is correlated with the water temperature, while previous studies have only suggested a relationship that was not statistically confirmed (12,21). In the analyses of 2000, R. solanacearum began to be detected in river water mostly in early July, when the temperature rose above 14°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the bacterium was not found in any of 134 water samples tested, including those originating from areas in which the bacterium was found in ware potato samples. It is noteworthy that outbreaks of the bacterium in several European countries (UK, The Netherlands, Belgium, France, Spain) during the past two decades have been mostly associated with contamination of surface water used for irrigation, or the use of irrigation water from sources in which infected S. dulcamara was found to be growing (Janse, 1996;Grousset et al, 1998;Elphinstone et al, 1998;Caruso et al, 2000). Furthermore, Urtica dioica has also been reported to be a reservoir of the bacterial wilt pathogen (Wenneker et al, 1999).…”
Section: Biovar Determinationmentioning
confidence: 99%